Loading...

into f(x) = (x+a)… - QuestionCove
OpenStudy (anonymous):

into f(x) = (x+a)/b g(x) = cx - d So that they are inverses, meaning that the x and y values are reversed. For example If a = 2 and b = 3 we would get F(x) = (x + 2)/3 and g(x) = 3x - 2 Part 2 To prove this you would switch the x and y values and solve for x . Remember that y is the same as f(x) and g(x). Part 3 To evaluate g(f(x)) you substitute f(x) for x. In my example it would be 3((x+2)/3) -2. You then simplify it to find that f(f(x)) = x Part 4 You make an input output chart for each function and you will see that the x and y values are just reversed. Need help

2 years ago
Similar Questions: